Characterization of the sensory, physical, chemical, and microbial quality of microwave-assisted, thermally pasteurized fried rice during storage - Montero Díaz, María Laura (2020)
Companies producing ready-to-eat (RTE) meals are looking for processing alternatives that allow them to gain presence in the supermarket chill section. Microwave-assisted pasteurization systems (MAPS) offer the potential to produce safe, high-quality foods. This research examined sensory, physical, chemical, and microbial changes in fried rice processed with MAPS and stored at 7 °C over a 6-week storage period. Additional fried rice samples (cooked but not MAPS-processed) were stored at –31 °C and were used as the control. Randomly selected trays of each type of rice were analyzed at 1, 4, and 6 weeks of storage. Aroma, appearance, taste/flavor, texture, mouthfeel, and aftertaste were evaluated by a semitrained sensory panel with rate-all-that-apply questions. The type of rice treatment (MAPS or control) significantly influenced sensory attributes (P < 0.05), with firm texture attribute of the egg being more intense in the MAPS-rice compared to the control. In addition, storage time affected the sensory modalities of both rice samples, including aroma, appearance, and taste/flavor (P < 0.05). No spoilage-associated sensory attributes were detected in the MAPS-rice during storage. At each examination point, various physical, chemical, and microbial analyses were conducted for the MAPS- and control rice. From the physical and chemical perspective, the MAPS-rice did not present relevant changes over the period tested. Microbial growth was the main cause of spoilage of the MAPS-rice; however, MAPS was able to extend the regular 5-day shelf life of a chilled fried rice meal to 6 weeks, demonstrating the potential of this technology for the RTE industry.